IS THE COMMUNITY OF ANESTHESIOLOGISTS AND EMERGENCY PHYSICIANS READY FOR THE SYSTEM OF CONTINUOUS MEDICAL EDUCATION? - Yu. S. Polushin; K. G. Shapovalov (Вестник анестезиологии и реаниматологии, 2018)
Reforming of medical personnel training in Russia is on-going and inevitable. However, the transfer to continuous medical education causes numerous questions in practicing medical specialists. The objective is to assess the awareness of anesthesiologists and emergency physicians of future reforms of medical education, their readiness to learning. Methods: 10 questions about important aspects of transfer to continuous medical education were compiled and placed on the website of Anesthesiologists and Emergency Physicians Association (http://ассоциация-ар.рф). Almost 100 specialists from various regions participated in this voluntary anonymous inquiry. Results show the lack of information on continuous medical education among practicing doctors and poor readiness of some specialists to the planned reforming of medical training, as well as the risk that some specialists will stop working in medicine. Conclusion. Some deeper explanation of the reforms is needed, the legislature is to be improved and opinions of specialists are to be monitored.